2010
DOI: 10.1501/vetfak_0000002432
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant follicle stimulating hormone (rFSH) on some fertility parameters in Awassi ewes synchronized with PGF2α in the breeding season

Abstract: Summary:The present study was aimed at the investigation of the effects of Recombinant Follicle Stimulating Hormone (rFSH) on fertility in Awassi ewes synchronized with PGF 2 α in the breeding season. The fifty thoroughbred Awassi ewes used in the study were injected twice with 0.150 mg of Tiaprost (PGF 2 α, Iliren®) at a 10-day interval. Following the second PGF 2 α injection, the ewes were randomly distributed into two equal groups. The ewes included in the first group were not subjected to any additional in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…Conception rate was 100% in all groups with no significant difference among each group (P> 0.05). These results were in agreement with results gained by Yavuzer et al (2010) who used double injection of PGF 2 α, 10 days apart with or without injection of follicle stimulating hormone (FSH) and obtained 100 and 95% conception rates, respectively. In contrast to present investigation, Zohara et al (2014) observed conception rate was 75% in Bangladesh indigenous ewes synchronized by two doses of PGF 2 α (175μg).…”
Section: Reproductive Responsessupporting
confidence: 91%
“…Conception rate was 100% in all groups with no significant difference among each group (P> 0.05). These results were in agreement with results gained by Yavuzer et al (2010) who used double injection of PGF 2 α, 10 days apart with or without injection of follicle stimulating hormone (FSH) and obtained 100 and 95% conception rates, respectively. In contrast to present investigation, Zohara et al (2014) observed conception rate was 75% in Bangladesh indigenous ewes synchronized by two doses of PGF 2 α (175μg).…”
Section: Reproductive Responsessupporting
confidence: 91%